2019
DOI: 10.1136/bmjopen-2018-026162
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrics properties of the Team Interaction Scale and influencing factors of team interaction of tertiary hospital physicians in China: a cross-sectional study

Abstract: ObjectivesTo administer a cross-cultural adaptation of the Team Interaction Scale (TIS), test its psychometric properties and investigate influencing factors of team interactions in a physician population in Chinese tertiary hospitals.DesignCross-sectional survey.SettingsTwo rounds of surveys, a pilot and a large sampling survey, were conducted in two and nine tertiary hospitals, respectively, in Liaoning Province, China.ParticipantsIn the pilot survey, 363 of 390 physicians sampled were included in the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Five out of the six remaining studies investigate the inputprocess relationship via other questionnaires (32,34,38,41,47). Similar to the findings of the previous HSOPSC and SAQ studies, female doctors perceive significantly better team interaction (e.g., communication, coordination, and mutual help) than male doctors (47). Profession, department, and age also influence healthcare professionals' ratings on team processes.…”
Section: Relationship Between Inputs and Processesmentioning
confidence: 56%
See 3 more Smart Citations
“…Five out of the six remaining studies investigate the inputprocess relationship via other questionnaires (32,34,38,41,47). Similar to the findings of the previous HSOPSC and SAQ studies, female doctors perceive significantly better team interaction (e.g., communication, coordination, and mutual help) than male doctors (47). Profession, department, and age also influence healthcare professionals' ratings on team processes.…”
Section: Relationship Between Inputs and Processesmentioning
confidence: 56%
“…The overall teamwork scores of internal medicine nurses are significantly lower than those of surgical nurses (34, 38). However, internal medicine doctors score team interaction significantly higher than surgeons (47). Staff younger than 30 years perceive better overall teamwork than those older than 30 years in one study (38) but score team cohesion significantly lower than those between 40 and 50 years old in another study (41).…”
Section: Relationship Between Inputs and Processesmentioning
confidence: 86%
See 2 more Smart Citations
“…In many studies, being young, having semi-work experience, and intense work predisposes one to burn-out in tertiary care hospitals [28]. In another study conducted in China, excessive burn-out was observed in doctors working in the emergency department in tertiary hospitals with less than 10 years of experience [30].…”
Section: (Sd) Medianx (Sd) Medianmentioning
confidence: 99%